2016
DOI: 10.1038/onc.2016.287
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferase 5 functions as an epigenetic activator of the androgen receptor to promote prostate cancer cell growth

Abstract: Protein arginine methyltransferase 5 (PRMT5) is an emerging epigenetic enzyme that mainly represses transcription of target genes via symmetric dimethylation of arginine residues on histones H4R3, H3R8 and H2AR3. Accumulating evidence suggests that PRMT5 may function as an oncogene to drive cancer cell growth by epigenetic inactivation of several tumor suppressors. Here we provide evidence that PRMT5 promotes prostate cancer cell growth by epigenetically activating transcription of the androgen receptor (AR) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 49 publications
6
139
0
Order By: Relevance
“…The BTG2 protein increase induced by PRMT5 inhibition was blocked when cells were pretreated with an ERK inhibitor (PD0325901). In addition, Chen et al [27] reported that PRMT5 activity was necessary for its phenotypes. To provide additional evidence for this hypothesis, we used GSK591 to block PRMT5 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The BTG2 protein increase induced by PRMT5 inhibition was blocked when cells were pretreated with an ERK inhibitor (PD0325901). In addition, Chen et al [27] reported that PRMT5 activity was necessary for its phenotypes. To provide additional evidence for this hypothesis, we used GSK591 to block PRMT5 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Sp1 can interact directly with the transcriptional machinery (TFIID) to initiate transcription. However, more recently Sp1 was found to recruit the chromatin modifying enzymes Brg1 and protein arginine methyltransferase, PRMT 5, to the AR promoter (Deng et al 2017). This epigenetic regulation was correlated with increased AR expression and prostate cancer cell growth.…”
Section: Role Of Transcription Factor Sp1mentioning
confidence: 99%
“…In particular, PRMT5-mediated posttranslational histone modification significantly affects gene expression and ultimately induces abnormal cell growth and proliferation (38,39). Overexpression or dysregulation of PRMT5 has been reported in a number of cancers, including ovarian, breast, lung, lymphoid, lymphoma, melanoma, colon, gastric, prostate, and bladder cancer and germ cell tumors (13,40,41). Negative regulation of histone arginine methylation by M6CK raises the possibility that TRPM6 could be used as an endogenous PRMT5 inhibitor to suppress some tumors.…”
Section: Discussionmentioning
confidence: 99%